UNDERSTANDING AND PRACTICE OF SOME ARTICLE IN THE LABOR LAW OF EMPLOYERS AND YOUTH MIGRANTS IN INFORMAL SECTOR IN HANOI - NGUYEN, Thi Thieng (ĐHQGHN, 2015)
This article is based on “Research on youth migrants working in the informal sector in Hanoi” that was implemented by the Institute for Population and Social Studies – The National Economics University (IPSS-NEU) and with the cooperation, the both technical and financial support from Plan in Vietnam - Hanoi Programme Unit. The objective of this study is analyzing the situation of young migrants working in the informal sector at both the departure and destination areas, then based on the results propose recommendations. This study used a combination of two types of information from the studies of already available documents and the primary data (conducted in 2009). The primary data were collected through: the quantitative survey (903 youth migrants aged 15-24 working in the informal sector in Ha Hoi); and the qualitative survey (46 in-depth interviews (IDIs) and 06 focus group discussions (FGDs) in Hanoi, 18 IDIs and 12 FGDs in departure areas (3 provinces: Bac Giang, Phu Tho and Thai Nguyen)). This article aims to describe the understanding and practice of the employer and the youth migrants in the informal sector in Hanoi about the Labor Law.